The influence of job rotation practices on employee motivation: A study among mobile network companies' employees in Yemen - Al-Nashmi, Murad Mohammed; Almoayad, Amani Abdullah Ahmed (Scientific Research Center, 2015)
Although job rotation (JR) has been considerably tackled by many scholars in the literature, the influence of JR on the employee motivation (EM) has been given less remarkable attention. This study examines the influence of the five components comprising JR (i.e., overall JR, training and capacity development, job design, career development strategy, and company regulations or systems and procedures) on EM in mobile network companies operating in Yemen. It reviews the literature concerning JR with its components, and EM in mobile network companies operating in Yemen. The framework and the hypotheses of the study are postulated to examine empirically the impact of JR on EM. 250 questionnaires were disseminated to individual employees among the four mobile network companies in Yemen and only 205 valid questionnaires were analyzed as the final sample size using both descriptive and inferential statistical analyses. Obtained results revealed that the five components of JR have positive significant relationships with EM in mobile network companies operating in Yemen. Moreover, the most influential components of JR on the EM is the company regulations (i.e., systems & procedures) followed by the training and capacity development.